PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEMANDIRIAN GAPOKTAN - Wery Belem; Sunarru Samsi Hariadi; Sri Peni Wastutiningsih (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
This study was conducted to assess the effect of the transformational leadership toward Gapoktan independence. This study is a descriptive research, which is a type of research that aims to describe something. The analysis in this study is done by combining the quantitative approach that is supported by qualitative approach.The results showed that there are significant effect of transformational leadership against the Gapoktan independence. It is based on statistical tests were performed with simple linear regression. The above results confirm the contribution of the transformational leadership in support for Gapoktan independence realization. The implication is the extent to which the leader can actualize values in transformational leadership, then it will have an impact on the realization of Gapoktan independence. Keywords: the transformational leadership, gapoktan independence